The large landscape of supernova, GRB, and cocoon interactions. Issue 3 (17th March 2022) - De Colle, Fabio; Kumar, Pawan; Hoeflich, Peter
ABSTRACT: Long gamma-ray bursts (LGRBs) are associated to the collapse of a massive star and the formation of a relativistic jet. As the jet propagates through the star, it forms an extended, hot cocoon. The dynamical evolution of the jet/cocoon system and its interaction with the environment has been studied extensively both analytically and numerically. On the other hand, the role played by the supernova (SN) explosion associated with LGRBs in determining the outcome of the system has been barely considered. In this paper, we discuss the large landscape of outcomes resulting from the interaction of the SN, jet, and cocoon. We show that the outcome depends mainly on three time-scales: the times for the cocoon and SN shock wave to break through the surface of the progenitor star, and the time needed for the cocoon to engulf completely the progenitor star. The delay between the launch of the SN shock moving through the progenitor star and the jet can be related to these three time-scales. Depending on the ordering of these time-scales, the jet-cocoon might propagate inside the SN ejecta or the other way around, and the outcome for the properties of the explosion would be different. We discuss the imprint of the complex interaction between the jet-cocoon and the SN shock on the emergent thermal and non-thermal radiation.